2018
DOI: 10.5751/es-10282-230248
|View full text |Cite
|
Sign up to set email alerts
|

The network structure of multilevel water resources governance in Central America

Abstract: The acceleration of changes in global water resource systems is exacerbating the ability of governance institutions to adapt, particularly in developing world regions. We highlight one of the key challenges to resilience in environmental governancecoordinating governance processes within and across multiple interacting geographic levels-and investigate structures of local, regional, and multilevel water governance networks using empirical data from Central America. We examined hypotheses of multilevel governan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 65 publications
0
24
0
1
Order By: Relevance
“…Our propositions in Table 1 are consequently expressed as such building blocks. ERGM models have been extensively used for evaluating networks in different cases and contexts (Berardo & Lubell, 2016; Bodin & Nohrstedt, 2016; Hamilton et al., 2019; Hileman & Lubell, 2018; Pittman & Armitage, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Our propositions in Table 1 are consequently expressed as such building blocks. ERGM models have been extensively used for evaluating networks in different cases and contexts (Berardo & Lubell, 2016; Bodin & Nohrstedt, 2016; Hamilton et al., 2019; Hileman & Lubell, 2018; Pittman & Armitage, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Resource distribution is required to establish the distributional fairness of the system, which is ultimately linked to legitimacy, institutional stability, and collaborative behavior (Berardo, 2013;Leach & Sabatier, 2005;Lubell, 2003). Within polycentric governance systems, different institutional or network structures may enable different governance goals (Hileman & Lubell, 2018;Levy & Lubell, 2018), but the relationships may be far from linear, and dependent on the trade-offs among those goals (Hamilton & Lubell, 2018). For instance, is learning more or less likely when bridging structures in an ecology of games operate in a context where the distribution of benefits that arise from cooperation are largely unequal?…”
Section: Functional Variationmentioning
confidence: 99%
“…However, we excluded all actors with only one partner, in order to focus on the core structures at the heart of the business ecosystem network. Previous research has demonstrated core network structures tend not to vary substantially across different data collection methods [ 62 ], and preserve the dominant features of the overall network [ 47 ]. After removing these actors, the business ecosystem comprises 455 actors and 1,455 collaborative ties ( Fig 2b ).…”
Section: Methodsmentioning
confidence: 99%